2012
DOI: 10.1111/j.1460-2466.2012.01664.x
|View full text |Cite
|
Sign up to set email alerts
|

Public Intimacy: Disclosure Interpretation and Social Judgments on Facebook

Abstract: This research examines how sociotechnical affordances shape interpretation of disclosure and social judgments on social networking sites. Drawing on the disclosure personalism framework, Study 1 revealed that information unavailability and relational basis underlay personalistic judgments about Facebook disclosures: Perceivers inferred greater message and relational intimacy from disclosures made privately than from those made publicly. Study 2 revealed that perceivers judged intimate disclosures shared public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
195
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(208 citation statements)
references
References 22 publications
10
195
0
1
Order By: Relevance
“…Under these circumstances, a higher level of perceived disclosure intimacy was found to be positively correlated to the development of ambient intimacy, which is in line with previous findings (Altman & Taylor, 1973;Rains et al, 2014;Utz, 2015b). Perhaps, similar to the results in Cozby's (1972) study, it is possible to observe a reverse U-shaped relationship between perceived disclosure intimacy and ambient intimacy: A certain level of disclosure intimacy is good for promoting ambient intimacy, but highly intimate self-disclosure, when perceived as inappropriate, would probably backfire (Bazarova, 2012).…”
Section: Theoretical Implicationssupporting
confidence: 90%
See 2 more Smart Citations
“…Under these circumstances, a higher level of perceived disclosure intimacy was found to be positively correlated to the development of ambient intimacy, which is in line with previous findings (Altman & Taylor, 1973;Rains et al, 2014;Utz, 2015b). Perhaps, similar to the results in Cozby's (1972) study, it is possible to observe a reverse U-shaped relationship between perceived disclosure intimacy and ambient intimacy: A certain level of disclosure intimacy is good for promoting ambient intimacy, but highly intimate self-disclosure, when perceived as inappropriate, would probably backfire (Bazarova, 2012).…”
Section: Theoretical Implicationssupporting
confidence: 90%
“…When it comes to broadcasting self-disclosure on social media, Bazarova (2012) found that intimate selfdisclosure in public might be treated as inappropriate and therefore reduced social attraction. Baruh and Cemalcılar (2015) found that intimate self-disclosure on Twitter had negative effects on interpersonal attraction, even though high-intimacy disclosure attracted more attention compared to low-intimacy disclosure.…”
Section: Disclosure Intimacymentioning
confidence: 99%
See 1 more Smart Citation
“…A simple example is that the design elements of a chair suggest to a person that the object could be used for sitting. An affordance approach can be useful for research and intervention design because while popular websites may change, issues that may arise with use of these websites can be predicted by considering key concepts such as anonymity that are inherent in the design of the website (Bazarova, 2011;Choi & Toma, 2014;Halpern & Gibbs, 2013;Steinfield, Ellison, & Lampe, 2008).…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Disclosure has a significant role in online impression formation (e.g., Antheunis, Valkenburg, & Peter, 2007), the development of intimacy (Bazarova, 2012), and friendship quality (Valkenburg & Peter, 2009a). Less, however, is known about the communication dynamics surrounding self-disclosure in online interaction, that is, the responses that people receive to their online self-disclosure.…”
Section: Introductionmentioning
confidence: 99%